ANALISIS PENGARUH TEMPERATUR PIROLISIS LIMBAH PLASTIK HIGH DENSITY POLYETHILENE (HDPE) TERHADAP LAJU REAKSI HASIL BIO OIL SEBAGAI BAHAN BAKAR ALTERNATIF - Indrayani, Novi Laura; Sadiana, Riri; Novianto, Niko Alifin; Syahputra, Novin (Jurnal Ilmiah Teknik Mesin, 2021)
Plastics are synthetic polymer compounds formed from the polymerization of small molecules(monomers) composed of hydrocarbon bonds. The use of plastic waste as a material to produce fueloil is an alternative that can increase the economic value of plastic waste, besides that it can alsosolve one of the environmental problems. This study aims to analyze the characteristics of fuel oilproduced from plastic waste type High Density Poly Ethylene (HDPE) with the pyrolysis process. Theresearch methodology variables include; the pyrolysis time was 120 minutes and the pyrolysistemperatures were 390oC, 410oC, 430oC, and 450oC. The test of the pyrolysis oil is based on theflash point. Furthermore, the calculation of the reaction kinetics using the Arrhenius Equationmethod. The optimum temperature for HDPE plastic pyrolysis is at a temperature of 450Â°C with aconversion efficiency of 59.3% wt. The value of the reaction rate constant obtained is k = 7.3 x 109 .e(117.013/R.T).